2023
DOI: 10.3389/fnut.2023.1175622
|View full text |Cite
|
Sign up to set email alerts
|

Turmeric supplementation improves markers of recovery in elite male footballers: a pilot study

Abstract: Football match-play causes muscle damage and provokes an inflammatory response. Rapid recovery is paramount to optimising subsequent performance and reducing injury risk. Turmeric contains high concentrations of curcumin, a polyphenol that has been shown to reduce muscle damage and soreness post-exercise in recreational exercisers. However, it is unknown whether a curcumin-containing supplement can support elite footballers recovery between matches. This applied study explored whether a turmeric supplement cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 40 publications
(67 reference statements)
3
3
0
Order By: Relevance
“…Plasma [CRP] increased 40 h post-match, but the increase was attenuated in the supplementation period compared to the control period. This provides tentative support to our previous study that found a turmeric-containing supplement (70 g/d) reduced [CRP] in elite male footballers compared to a non-supplementation group [ 23 ]. CRP is a protein secreted by the liver that correlates with systemic inflammation [ 52 ].…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Plasma [CRP] increased 40 h post-match, but the increase was attenuated in the supplementation period compared to the control period. This provides tentative support to our previous study that found a turmeric-containing supplement (70 g/d) reduced [CRP] in elite male footballers compared to a non-supplementation group [ 23 ]. CRP is a protein secreted by the liver that correlates with systemic inflammation [ 52 ].…”
Section: Discussionsupporting
confidence: 87%
“…In the current study, daily supplementation persisted through the pre- and post-exercise period. The curcumin dose was lower than a previous study [ 23 ] but similar to [ 20 ], or greater than [ 48 ], other studies that have reported a positive effect on subjective soreness after exercise. Contextual and external factors can inevitably influence a subjective perception of soreness, and these factors are difficult to control in elite sportspeople.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations